RPS15 mutations rewire RNA translation in chronic lymphocytic leukemia - Ntoufa, Stavroula; Gerousi, Marina; Laidou, Stamatia; Psomopoulos, Fotis; Tsiolas, Georgios; Moysiadis, Theodoros; Papakonstantinou, Nikos; Mansouri, Larry; Anagnostopoulos, Achilles; Stavrogianni, Niki; Pospisilova, Sarka; Plevova, Karla; et al. (Blood advances, 2021)
Recent studies of chronic lymphocytic leukemia (CLL) have reported recurrent mutations in the RPS15 gene, which encodes the ribosomal protein S15 (RPS15), a component of the 40S ribosomal subunit. Despite some evidence about the role of mutant RPS15 (mostly obtained from the analysis of cell lines), the precise impact of RPS15 mutations on the translational program in primary CLL cells remains largely unexplored. Here, using RNA sequencing and ribosome profiling, a technique that involves measuring translational efficiency, we sought to obtain global insight into changes in translation induced by RPS15 mutations in CLL cells. To this end, we evaluated primary CLL cells from patients with wild-type or mutant RPS15 as well as MEC1 CLL cells transfected with mutant or wild-type RPS15. Our data indicate that RPS15 mutations rewire the translation program of primary CLL cells by reducing their translational efficiency, an effect not seen in MEC1 cells. In detail, RPS15 mutant primary CLL cells displayed altered translation efficiency of other ribosomal proteins and regulatory elements that affect key cell processes, such as the translational machinery and immune signaling, as well as genes known to be implicated in CLL, hence highlighting a relevant role for RPS15 in the natural history of CLL.
Keywords: mutace; Leukemia, Lymphocytic, Chronic, B-Cell; Humans; Mutation; lidé; RNA; Ribosomal Proteins; ribozomální proteiny; chronická lymfatická leukemie